4 - A Review of Academic Freedom in Africa through the Prism of the UNESCO’s 1997 Recommendation - Karran, Terence; Beiter, Klaus; Appiagyei-Atua, Kwadwo (Journal of Higher Education in Africa, 2022)
An assessment of the level of compliance of the UNESCO Recommenda- tion in Europe, Australia, USA and other jurisdictions indicates that the document has been honoured more in its breach than in its observance. Having returned to an ethos of a democratic culture and a refinement of the role of the university in the globalization era, it is time for Africa also to be assessed on the level of compliance with the UNESCO Recommendation. This assessment is done based on four indicators identified in the UNESCO Recommendation: institutional autonomy, institutional governance, indi- vidual rights and freedoms, and tenure. The conclusion reached is that academic freedom has indeed found its way back into African universities after its complete roll-back during the post-independence era. However, the university reforms undertaken in the globalization era in many African universities have undermined greater respect for academic freedom and made hollow the gains made in the respect of freedom in this era.